The origin of the Czech broadside ballad in late humanism? - Malura, Jan (Bohemica Olomucensia, 2019)
The paper is focused on the origin of the Czech Broadside Ballad. The key period for the first development of the Czech broadside ballad was late humanism (1590-1620). The emergence of this phenomenon was largely influenced by leaflet news, which developed considerably in the Czech lands in the last decade of the 16th century. In addition to this, the sung news, sensational songs and other song genres began to be printed separately in late humanism. Already during this period, these songs had many of the typical features of the baroque broadside ballad (simple verse and style, considerable length, the sense of detail, and final moralizing). At the same time, however, they were connected with the so-called occasional poetry and other phenomena of the bourgeois literary life of late humanism. In the burgher class, a large group of recipients was being formed at this time, which can be referred to as the wider public (a social class with certain education that was interested in what was happening in society). Nevertheless, it was not until the baroque period that the broadside ballad became part of mass folk (popular) culture.
Keywords: broadside ballad; late humanism in the Czech lands; leaflet news; occasional poetry; bourgeois literary life; Simon Lomnicky z Budce